Theobromine-Based Synthetic Derivatives As Potential Inhibitors Of Dengue Virus Ii Serine Protease - Saqallah, Fadi Ghassan Mohammed (2023)
Dengue is an RNA viral disease that is spread across tropical and subtropical urbanised districts. Up to June 2022, more than 17,497 cases of dengue infections have been reported in Malaysia since the beginning of the year, which is considered an increment of 57.6% compared to the first six months of 2021. Moreover, up to date, there is no licensed drug treatment for the management of dengue infections. Dengue virus (DENV) uses the NS2B/NS3 protease to cleave its polyprotein throughout the virus’s replication and life cycle. Hence, inhibiting the viral protease can suppress the replication of DENV. Previously, some unpublished data by our group showed that Theobroma cacao inhibited the DENV2 protease. Theobromine is a naturally occurring alkaloid commonly found in Theobroma cacao. Theobromine has a purine chemical scaffold which resembles that of 19 famous antivirals, which are either commercially available or under clinical investigations, including acyclovir. Moreover, only a few studies have reported the synthesis of theobromine and its derivatives, but to date, none have been related to antiviral agents. In this study, a group of 137 theobromine-based hybrid molecules were designed by conjugating theobromine (at position °1; the secondary amine) with other commercially available chemical entities and compounds.